I’m pretty sure you would have to make them equal
1. 3x -10=7x+14
2. Add 10 to both sides
3. 3x=7x+24
4. Subtract the variable ( 7x ) from both sides
5. -4x=24
6. Divide -4/24
I hope I did it right let me know if any errors
5 + 2 = 7
1/4 + 3/4 = 1
7 + 1 = 8
Your answer is 8
Answer:
(b) (x, y) ⇒ (-x, y); (x, y) ⇒ (x + 1, y + 1)
Step-by-step explanation:
A graph shows the image is consistent with reflection over the y-axis
(x, y) ⇒ (-x, y)
and translation right 1, up 1
(x, y) ⇒ (x +1, y +1)
These transformations are listed in the second choice.
__
In the attachment, the original image is blue, the reflected image is purple, and the final translated image is red.
Hi! Let me help you!
- Remember, factoring looks like so:
- ab+ac=a(b+c)
- So, we need to find the greatest common factor (G.C.F.) of the polynomial.
- In this case, 6 is the GCF, so we factor it out:
- 6x²+66x+60
- Divide 6, 66 and 60 by 6:
- x²+11x+10
<u>Answer:</u>
x²+11x+10
Hope you find it helpful.
